REKONSEPTUALISASI ASAS PEMISAHAN HORISONTAL DALAM PERTAMBANGAN MINERAL DAN BATUBARA DI INDONESIA - Firmansyah, Arif (Universitas Wiralodra, 2022)
The principle of horizontal separation in the UUPA replaces the principle of vertical attachment adopted by the Civil Code. The principle of horizontal separation comes from the philosophy of customary law. The principle of horizontal separation separates the ground and whatever is adhere to the ground. So far, the principle of horizontal separation has only discussed the separation of land and buildings on it. This paper attempts to develop the concept of horizontal separation in mineral and coal mining. The concept of the horizontal separation principle in mineral and coal mining is implied in Article 92 of the Mineral and Coal (Minerba) Law which states that the holder of a Mining Business Permit (IUP) and a Special Mining Business Permit (IUPK) has the right to own minerals, including associated minerals or coal that has been produced if it has been produced. meet exploration fees or production operation fees, except for radioactive associated minerals. This article shows that ownership of minerals and coal is given to IUP and IUPK holders who have paid dues, thus the transfer of ownership to IUPK and IUPK holders can be interpreted to separate land rights from minerals and coal. This the concept of the principle of horizontal separation does not only separate land from plants and buildings on it but also separates soil from minerals and coal.